Early Exercise in Critically Ill Youth and Children, a Preliminary Evaluation: The wEECYCLE Pilot Trial*. Issue 11 (November 2017) - Choong, Karen; Awladthani, Saif; Khawaji, Adeeb; Clark, Heather; Borhan, ASM; Cheng, Ji; Laskey, Sam; Neu, Charmaine; Sarti, Aimee; Thabane, Lehana; Timmons, Brian W.; Zheng, Katina; et al.
Abstract : Objectives: To determine the feasibility of conducting a full trial evaluating the efficacy of early mobilization using in-bed cycling as an adjunct to physiotherapy, on functional outcomes in critically ill children. Design: Single center, pilot, randomized controlled trial. Setting: Twelve-bed tertiary care, medical-surgical PICU at McMaster Children's Hospital, Hamilton, ON, Canada. Patients: Children 3–17 years old who were limited to bed-rest with an expected PICU stay of at least 48 hours. Patients were excluded if they were at their baseline level of function, already mobilizing out of bed or expected to do so within 24 hours. Interventions: Patients were randomized in a 2:1 ratio to early mobilization using in-bed cycling in addition to usual care physiotherapy (cycling arm) or to usual care physiotherapy alone (control). Usual care was according to institutional practice guidelines. The primary outcome was feasibility and safety. Measurements and Main Results: Thirty patients were enrolled (20 to the cycling and 10 to control) over a 12-month period, at a 93.7% consent rate. The median (interquartile range) time from PICU admission to mobilization was 1.5 days (1–3) in the cycling arm and 2.5 days (2–7) in the control arm. Total duration of mobilization therapy in PICU was 210 (152–380) and 136 minutes (42–314 min) in cycling and control arms, respectively. Total number of PICU days mobilized was 5.0 (3–6) with cycling and 2.5 (2–4.8) with usual care. No adverse events occurred in either arm. The main threat to feasibility of mobilization was the availability of physiotherapists or research personnel. Conclusions: Early mobilization is safe and feasible in the PICU. In-bed cycling may facilitate greater duration and intensity of mobilization, in critically ill children. A full-scale randomized controlled trial is warranted to evaluate the efficacy of this intervention on PICU-acquired morbidities and functional outcomes in this population. Abstract : Supplemental Digital Content is available in the text.